MASLAHAH WASIAT WAJIBAH FOR ADOPTED CHILDREN WITH DIFFERENT RELIGIONS AND STEPCHILDREN - Wahyuni Retnowulandari (Jurnal Hukum PRIORIS, 2021)
The problem of Islamic inheritance is complicated, therefore Rasulullah Salalahu Alaihi Wassalam ordered his followers to learn the Science of Faraidh and spread the knowledge. It is because the implementation of Faraid is based on the principle of ijbari (Coercion) according to the Qur'an Surah An-nisaa: 13-14. However, the issue is a lot of inheritance ruling by judges are not in accordance with Sharia provisions. One of them is the ruling in which the Religious High Court Judge No. 136/Pdt.G/2013/PTA.Sby, the case of Keman Rachman's inheritance which gave wasiat wajibah to stepchildren who were not next of kin, as well as adopted children of different religious faith. Meanwhile, the Hadith of the Prophet forbade a Muslim to inherit from a non-Muslim and vice versa. Even in Indonesia, within the provisions of the Compilation of Islamic Law Article 171 letter C stipulates that, benefactors must be Muslim. With normative research that is descriptive and qualitative in analysis, it is hoped that it can be stipulated whether the part of the inheritance of the wasiat wajibah is maslahah. The results of this study are non-Muslim adopted children may not receive a mandatory will according to the concept of ash'aryah, as well as stepchildren who are not heirs. It would be better for them to be given a grant equivalent to the amount of zakat maal, which is 2.5%. so that it is more Maslahah for the rightful heirs. Keywords: Islamic inheritance law, wasiat wajibah , maslahah